Medical care for smoking cessation in general practitioners’ practice - M. V. Vershinina; A. A. Khomenya; O. A. Foronosova; V. A. Gudilin (Лечащий Врач)
In order to find out the doctors knowledge about effective methods of smoking cessation, a survey of 86 internists and general practitioners, as well as 14 residents was conducted. Results of the survey confirm the need for systematic training of doctors on effective smoking cessation.